Investigation of open cycle thermochemical energy storage system in building application - Zhang, Yanan (2020)
In this study, it is aimed to design, develop and evaluate a high-performance thermochemical energy storage (TES) system for building sectors, which is based on material, reactor and process investigations. The TES system can be integrated with and driven by any kind of low temperature sustainable energy sources (e.g. solar energy, wind energy, and waste heat recovery system) to reduce fossil fuel consumption and greenhouse gas (GHG) emissions. In achieving the aims, eight aspects have been set out as followed: 1) A comprehensive literature survey on potential TES materials; 2) Evaluation of the cooling and heat storage capacity of the proposed materials using IES; 3) Selection of salt hydrate mixture and host matrix sorbents; 4) By using SDT-Q600, MIP and SEM to perform material characterisation analysis; 5) Set up some small scale experiments to analyse the characteristics of selected composites; 6) Test the thermochemical performance in a designed small-scale reactor; 7) Design and test a TES prototype in lab under UK weather condition; 8) Economic, environmental and techno-social analyses of the designed TES system. In the initial experimental work, the three candidates were tested in the lab-scaled rig. V-CaCl2-LiCl showed the highest water uptake of 0.12g/g in the 1st discharging cycle, but in the 2nd discharging process was much lower. The water uptake of V-MgSO4-LiCl was 0.1g/g in 1st reaction process which was twice as the 2nd cycle that means V- MgSO4-LiCl is not suitable for multiple cycles, moreover, the small water loss in charging process led to low regeneration efficiency. V-MgSO4-CaCl2 with weight ratio of 1:1:2 showed good potential for using in open THS systems. Although the water uptake was less, the air outlet temperature can reach as high as 46.1 °C and the water uptake in 2nd cycle stayed very similar with discharging cycle 1. Thus, V- MgSO4-CaCl2 with weight ratio of 1:1:2 was chosen as the testing TES material in the prototype. An open TES prototype with 16 kg V-MgSO4-CaCl2 was numerically and experimentally investigated. In the original prototype, the system showed poor performance in the discharging/reaction process because of some design flaws with lower relative humidity level and the highest air supply temperature was 37.44 °C with reaction COP of 1.05-1.2. Then the designed prototype was modified and optimized by changing the holding plate and placing a humidifier in front of the centrifugal fan. After that the prototype gave satisfactory results with air outlet temperature was as high as 43.1 °C to supply 2.88 kWh heating energy with COP of 1-1.51. It will be used for short-term TES storage as the system can easily provide enough heating demand daily usage. The economic and environmental analyses results showed that TES system shows a quick payback period of 6.4 years and a large reduction of 2136.7kg/year on CO2 emissions compared with the conventional natural gas heating system. Technically and economically, the system has proven to be effective in reducing fossil fuel consumption and CO2 emission, so it is only a matter of time before these systems are installed in houses in the UK and globally.